2010
DOI: 10.1590/s1516-35982010000900007
|View full text |Cite
|
Sign up to set email alerts
|

Bromatological and fermentative characteristics of elephant grass silages with the addition of annato by-product

Abstract: -The objective of the present study was to evaluate the nutritional value of elephant grass (Pennisetum purpureum, Schum.) silages with the addition of 0; 4; 8; 12 and 16% of the by-product from SPU annato (Bixa orellana, L.) based on natural matter. A complete random design was used with four replications. The nutritional composition, pH, ammonical nitrogen and lactic, acetic, propyonic and butyric acids were determined. Levels of annato by-product had an increasingly linear effect on contents of dry matter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…The apparent CPD was not affected (P>0.05) by AB inclusion and had a mean of 0.79 g/kg, resulting in 127 g/day of mean digestible protein. The lack of influence of AB on protein digestibility was also reported by Moraes (2007) and Rêgo et al (2010). According to Pereira et al (2010a), the main site of AB protein digestion in the rumen, the food has 60% of rumen degradable protein.…”
Section: Intake and Digestibilitymentioning
confidence: 58%
See 2 more Smart Citations
“…The apparent CPD was not affected (P>0.05) by AB inclusion and had a mean of 0.79 g/kg, resulting in 127 g/day of mean digestible protein. The lack of influence of AB on protein digestibility was also reported by Moraes (2007) and Rêgo et al (2010). According to Pereira et al (2010a), the main site of AB protein digestion in the rumen, the food has 60% of rumen degradable protein.…”
Section: Intake and Digestibilitymentioning
confidence: 58%
“…Moraes (2007) and Clementino (2008) observed that increased levels of AB promoted a linear increase in DMI (kg/day; %BW; g/kg 0.75 ) by goats and sheep. In a study evaluating the nutritive value of elephant grass silages added to AB, Rêgo et al (2010) also observed a linear increase in DMI (g/day) with increased levels of AB silage. In the three studies mentioned, AB replaced bulky diets, thus influencing positively the nutritive value of experimental diets and increasing the nutrient density.…”
Section: Intake and Digestibilitymentioning
confidence: 88%
See 1 more Smart Citation
“…De acordo com Rêgo et al (2010), o capim-elefante é capaz de mostrar elevado rendimento de forragem, quando convenientemente manejado e adubado.…”
Section: Forragensunclassified
“…Como o capim-elefante BRS Capiaçu, no momento ideal de corte apresenta teor de matéria seca de 16,5 a 19,7% (Pereira et al, 2016). Estudos envolvendo a adição de coprodutos ou resíduos com elevado teor de matéria seca na ensilagem têm sido conduzidos (Andrade et al, 2012;Bonfá et al, 2017;Borges et al, 2018;Ferreira et al, 2013;Martins et al, 2015;Monteiro et al, 2011;Rêgo et al, 2010).…”
Section: Introductionunclassified